Allocation of paleochannels in sand-clay sediments of middle Jurassic age in petrel software complex - A. A. Suslov; B. P. Vaynerman (Известия высших учебных заведений: Геология и разведка)
On the Tazovsko-Zapolyarny licence block (Tazovsky district of Yamalo-Nenets Autonomous District), according to the materials of the seismic survey (3D) in sand-clay sediments of Middle Jurassic age U2 , the channel elements, which lie at different depths and have a submeridional extension, are identified. The purpose of this work was to study the spatial position of the identified channel elements (paleochannels) and to construct them using the Petrel (Schlumberger) program. The paleochannel building technique is described in the Petrel program. Based on the obtained modelling data, the locations of increased reservoir thicknesses in the areas of paleochannels development were specified and the areas of new prospecting wells were planned. As a result of the seismic data (3D) processing, three systems of paleochannels located on different hypsometric marks and associated with the U2-2, U2-3 and U2-4 beds were allocated. On the basis of the correlation of the well sections of the U2 bed, the clay bulkheads between the assumed beds are allocated, and the U2-2, U2-3 and U2-4 beds are marked in the section. The structural modelling of the U2 bed was carried out using all available information and the Schlumberger Petrel software complex. Using the «Lithology» property (takes the values «collector»–0, «collector»–1), the 3D models of paleochannels have been created separately for the U2-2, U2-3 and U2-4 beds. The newly created models of paleochannels have been introduced into the total volume of the U2 bed.